Pengaruh Perputaran Piutang Usaha terhadap ROA pada Perusahaan Tekstil yang Terdaftar di BEI Periode 2014-2018 - Ermi Nilam Sari; Fatmi Hadiani; Radia Purbayati (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
This research was conducted to test the level of influence of receivable turnover against Return On Asset in the sub-sector companies of textile and garment listed on Indonesia Stock Exchange (IDX) period 2014-2018. The objects used in this research are the finansial statements of textile and garment companies listed on Indonesia Stock Exchange (IDX) period 2014-2018. The population in this research amounted to 22 textile and garment companies listed on the Indonesia Stock Exchange (IDX) and 6 samples were taken using purposive sampling techniques. The type of data used in this research is secondary data obtained from the company’s official website. The independent variable used in this research is receivable turnover, whereas for the dependent variable used in this research is return on asset. The data analysis techniques used in this research are descriptive statistics analysis, simple linear regression analysis, and hypothesis testing using SPSS software. The result indicate that the receivable turnover significant on return on asset with influence rate of 20.3%, while the remainder was 79.7% influenced by other factors outside this research.